The motorbike book the definitive visual history (Dorling Kindersley Limited, 2012)
'The Motorbike Book' is all about the men, machines and landmark technology behind the most iconic bikes from ACE to Zundapp. Featuring over 1,000 of the latest and greatest motorbikes in the world this is an amazing visual guide tracing their evolution from the 1910s right up to the superbikes of today. An action-packed ride through the history of the motorbikeThe Motorbike Book is all about the men, machines and landmark technology behind the most iconic bikes from ACE to Zundapp. Featuring over 1,000 of the latest and greatest motorbikes in the world this is an amazing visual guide tracing their evolution from the 1910s right up to the superbikes of today.All about the grit and the glory, The Motorbike Book takes a truly international view from Italy's Ducati to Japan's Suzuki and tells you just how famous marques like Honda and Harley-Davidson became household names. Plus, go on a virtual tour inside the engines of some of these legendary bikes to see just what powers their performance.If you're born to be wild then The Motorbike Book is the ultimate ride for you.